A survey of cardiopulmonary resuscitation in COVID-19 patients - Mukul C Kapoor; S SC Chakra Rao; Rasesh Dewan; Bernd W Böttiger (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: The novel coronavirus 2 (SARS-CoV-2) pandemic has placed severe resource constraints on hospitals. High mortality rates of the COVID-19 have overwhelmed the resuscitation services. The constant fear of virus infection during cardiopulmonary resuscitation (CPR) has placed severe restrictions on the resuscitation services. Reports of poor outcomes after CPR further dampened the spirits of CPR providers. Hence we surveyed CPR practices for COVID -19 patients across hospitals in India by health care providers. Material and Methods: An online survey using Google Forms was initiated to collect data on performance of CPR in diagnosed cases of COVID-19 after in-hospital cardiac arrest. The survey's web-link was publicized using social media, and participation sought of all personnel involved in CPR delivery in COVID-19 patients. The responses received were analyzed. The main outcome measured were determination of the percentage of COVID-19 patients discharged home who were administered CPR. Results: There were 248 responses from different parts of India. At the time of cardiac arrest, 194 victims had diffuse lung infiltrates, 22 had mild lung disease, while 32 had no documented lung lesion. Twenty-five victims had evidence of pulmonary embolism, 39 had cardiac involvement, and 3 had brain involvement. Return of spontaneous circulation (ROSC) was achieved in 59.27% of cases but ROSC sustained in only 22.59%. 7.25% of patients, who received CPR, could be discharged home. Conclusion: The survey has shown reasonable survival rates after CPR administration in COVID-19 patients suffering from IHCA. We should not ignore the need to maximize live outcomes after CPR, even in COVID-19 patients.